Developing a Pancasila students' character instrument: Proof of construct validity and estimation of construct reliability - Wiwin Mistiani; Edi Istiyono; Amir Syamsudin; Nor Hasnida Md. Ghazali (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2024)
This study aims to prove construct validity and estimate construct reliability of the character scale of Pancasila students by using confirmatory factor analysis. The research approach used is quantitative with a sample of 200 high school students selected at random. This study measured the variables by six aspects, 15 indicators, and 20 questions. The six aspects include faith and piety to God Almighty, global nationality, cooperation, independence, critical reasoning, and creativity. The data analysis technique used is confirmatory factor analysis. The study results concluded that the instrument for assessing the character of Pancasila students in high school had a loading factor of more than 0.4 and a value of more than 0.96 which was declared valid and significant. Likewise, the instrument has been declared fit in testing the goodness of fit model. Thus, this finding indicates that the observed and performance covariance matrices are not significantly different. This study recommends a scale to measure the character of Pancasila students in senior high school.